Six long years: exploring resettlement as a durable solution for Rohingya refugees in Bangladesh - Mithun, Mahanam Bhattacharjee (Frontiers in Human Dynamics, 2023)
Rohingya refugees from Myanmar have been living in Bangladesh since the 1970s. Although some successful negotiations with the Myanmar government resulted in repatriation in the 1970s and 1990s, some refugees remained in Bangladesh. In 2017, after their large-scale exodus from Myanmar, Rohingya refugees have been living in Bangladesh for nearly 6 years. So far, none of the refugees have had a chance to go back to their motherland. This study constitutes an exploratory research endeavor using qualitative research methodologies. It explores resettlement as a durable solution option and provides a set of recommendations for ensuring the protection and upholding the dignity of refugees. It argues that any solution options should be based on consultations with the refugee population. The findings of this research also illustrate why resettlement pathways for the vulnerable members of the refugee community should be open to ensure protection and for providing opportunities in a third country in the absence of a viable repatriation process.